DIFFICULTIES IN DIFFERENTIAL DIAGNOSTICS OF RESPIRATORY TUBERCULOSIS AND SARCOIDOSIS - M. V. Pavlova; M. A. Belokurov; I. V. Chernokhaeva; O. A. Yakunova; A. R. Kozak; V. A. Tsinzerling (Туберкулез и болезни лёгких)
TB doctors and pulmonologists are very well familiar with the issue of differential diagnostics between pulmonary tuberculosis and sarcoidosis. Despite the introduction of new diagnostic tools for disseminated diseases, the absence of pathognomonic, clinical, X-ray and morphological signs of the disease remains to be the big problem resulting in the significant number of diagnostic mistakes (60-75%). The Mantoux test with 2 TU is still used for differential diagnostics between tuberculosis and sarcoidosis. Till present among immunological tests the skin tuberculin test has remained to be the only one for tuberculosis diagnostics. However recently some new highly informative immunological tests have appeared allowing diagnosing tuberculosis on a higher level and thus giving up Mantoux test with 2 TU. The article presents the clinical case confirming the value of immunological tests in differential diagnostics between sarcoidosis and tuberculosis.